KEWENANGAN PEMERINTAH KOTA LHOKSEUMAWE DALAM PENGELOLAAN DESTINASI PARIWISATA BERDASARKAN QANUN ACEH NOMOR 8 TAHUN 2013 TENTANG KEPARIWISATAAN - riana dewi; Hasan Basri; Yusrizal Y (Fakultas Hukum Universitas Malikussaleh, 2020)
This study aims to find out how the implementation of the authority of the Lhokseumawe City Government in the Management of Tourism Destinations based on Aceh Qanun Number 8 of 2013 concerning Tourism. This research method is a qualitative method in the form of normative legal research, namely research that puts the law in place to answer legal problems faced through a statutory approach contained in related articles. The nature of this research is descriptive-analytic by using library research. Based on this research, it is explained that the Lhokseumawe City Government as the person in charge and plays a very important role in the management of tourist attractions must control the tourist environment. Barriers to managing tourism destinations are due to the government's lack of firmness to impose sanctions on the community. Efforts are being made by the Government by frequently conducting raids at tourist attractions in Lhokseumawe City. The writer's suggestion in this study is that it is hoped that the Lhokseumawe City Government will further improve supervision of tourist attractions and it is advisable to immediately impose sanctions on people who do and allow Lhokseumawe City Regional tourist attractions to be polluted by acts that are not polite and violate the Shari'a. Islam. Keywords: Government Authority, Management, Tourism Destinations, Aceh Qanun Number 8 of 2013.